Gene silencing by siRNA nanoparticles synthesized via sonochemical method - Shimanovich, Ulyana (2014)
The knowledge that small RNAs can affect gene expression has had a tremendous impact on basic and applied research, and gene silencing is currently one of the most promising new approaches for disease therapy. However, RNAs cannot easily penetrate cell membranes, therefore RNA delivery become one of the major challenges for gene silencing technology. In the current paper we discuss a general approach for converting siRNA molecules into a dense siRNA nanoparticles using environmentally friendly sonochemical method. The RNA nanoparticulation enhance its gene-silencing activity in vascular bovine endothelial as well as in cancer 293T/GFP-Puro cell lines without causing any toxic effect. We show that ultrasonic waves do not lead to RNA degradation or any changes in its chemical structure. Moreover, sonochemically produced siRNA nanoparticles have been shown to be resistant to a variety of environmental stresses including pH levels, enzymes and temperatures, hence solving problem of the short half-life of the RNA molecules. As the siRNA nanoparticles are biocompatibile and biodegradabile, and their RNA release properties may be controlled within limits, sonochemical formation of siRNA nanoparticles represent a new promising approach for generation of functional bionano materials.